CreER activation transiently disrupts angiogenesis by reducing proliferation and promoting apoptosis in vascular endothelial cells - Elena Ioannou; Mengmeng Dong; Victoria S. Rashbrook; Christiana Ruhrberg; Martina Rudnicki (Angiogenesis, 2026)
Tamoxifen-inducible gene targeting in mice with estrogen receptor-dependent Cre (CreER) recombinase has enormously advanced vascular biology research. However, CreER activation under the control of vascular endothelial promoters causes off-target effects that impair the vascularization of the retina, a widely used model to study the molecular and cellular mechanisms of angiogenesis. Although ubiquitously expressed CreER is also used to study retinal angiogenesis, it remains unknown whether it causes similar or more severe off-target effects compared to endothelial-selective CreER activation. Moreover, the molecular and cellular processes disrupted by CreER activation in endothelial cells remain to be identified. Here, we demonstrate that ubiquitous CreER activation in postnatal mice decreases body growth and impairs retinal angiogenesis. We further show that CreER activation slows endothelial cell proliferation and promotes apoptosis concomitant with p21/CDKN1A upregulation in the angiogenic retina, although retinal vasculature progressively normalizes. By contrast, CreER activation in quiescent adult retinal vasculature did not induce endothelial cell apoptosis or p21 activation. Altogether, our findings indicate that ubiquitous promoters should be avoided to drive CreER expression when studying gene function during retinal angiogenesis, and that CreER activation controls, although essential to account for endothelial apoptosis and proliferation defects in short-term studies, may be less critical for adult vascular studies.

Active interactions between animals and technology: biohybrid approaches for animal behaviour research - M. Papadopoulou; M. Ball; P. Bartashevich; A.L.J. Burns; V. Chiara; M.A. Clark; B.R. Costelloe; M. Fele; F. French; S. Hauert; M.K. Heinrich; J.E. Herbert-Read; et al. (Animal Behaviour, 2025)

The 2011 Great East Japan earthquake: fragility of Japanese buildings to ground shaking - I. Ioannou; S. Bertelli; R.E. Chandler; S. Ohno; A. Shibayama; A. Suppasri; T. Rossetto (Bulletin of Earthquake Engineering, 2025)
The quality of post-disaster data directly impacts the reliability of empirical fragility curves. Many seismic studies rely on estimated, rather than measured, ground motion intensity due to the limited number of recording stations. However, this study utilizes a unique database of over 7,817 buildings surveyed near 37 ground motion stations in the prefectures of Fukushima, Miyagi and Iwate Prefectures following the 2011 Great East Japan earthquake. This research examines damage data inland of the tsunami inundation zone, which has received little attention. A flexible Bayesian framework is employed to construct fragility curves, accounting for data overdispersion and uncertainty in the actual level of ground motion intensity experienced by the buildings. Despite large uncertainties, the results reveal that post-2000 buildings demonstrated superior seismic performance, while pre-1981 buildings were the most vulnerable. Contrary to observations from the 1995 Kobe earthquake, heavy steel frame buildings emerged as the most susceptible to damage, whereas wooden buildings performed similarly to reinforced concrete and light steel frame structures. Additionally, a sensitivity analysis indicates that the difference between the recorded ground motion intensity and the level actually experienced by the buildings surveyed in the station’s vicinity has a negligible impact on the fragility curves.

An accurate two-stage deep machine learning aided air quality estimation based on multiple gases from aerial images - Iacovos Ioannou; Prabagarane Nagaradjane; Ala Khalifeh; Vasos Vassiliou; Janardhan M; Kaavya S; Vibish Kashyap B; Andreas Pitsillides (Air Quality, Atmosphere & Health, 2025)

Insecticide resistant mosquitoes remain thermal stress resistant, without loss of thermal plasticity - Charalampos S. Ioannou; Eleni C. Savvidou; Lemonia Apocha; John S. Terblanche; Nikos T. Papadopoulos (Science of The Total Environment, 2024)

Central versus peripheral mechanisms of cold-induced vasodilation: a study in the fingers and toes of people with paraplegia - Lydia Tsoutsoubi; Leonidas G. Ioannou; Billie K. Alba; Stephen S. Cheung; Hein A. Daanen; Igor B. Mekjavic; Andreas D. Flouris (European Journal of Applied Physiology, 2023)
Purpose This study examined physiological and perceptual parameters related to cold-induced vasodilation (CIVD) in the fingers and toes of people with paraplegia and compared them with responses observed in able-bodied individuals. Methods Seven participants with paraplegia and seven able-bodied individuals participated in a randomized matched-controlled study involving left-hand and -foot immersion in cold water (8 ± 1 °C) for 40 min during exposure to cool (16 ± 1 °C), thermoneutral (23 ± 1 °C), and hot (34 ± 1 °C) ambient conditions. Results Similar CIVD occurrence was observed in the fingers in the two groups. In toes, three of the seven participants with paraplegia revealed CIVDs: one in cool, two in thermoneutral, and three in hot conditions. No able-bodied participants revealed CIVDs in cool and thermoneutral conditions, while four revealed CIVDs in hot conditions. The toe CIVDs of paraplegic participants were counterintuitive in several respects: they were more frequent in cool and thermoneutral conditions (compared to the able-bodied participants), emerged in these conditions despite lower core and skin temperatures of these participants, and were evident only in cases of thoracic level lesions (instead of lesions at lower spinal levels). Conclusion Our findings demonstrated considerable inter-individual variability in CIVD responses in both the paraplegic and able-bodied groups. While we observed vasodilatory responses in the toes of participants with paraplegia that technically fulfilled the criteria for CIVD, it is unlikely that they reflect the CIVD phenomenon observed in able-bodied individuals. Taken together, our findings favor the contribution of central over peripheral factors in relation to the origin and/or control of CIVD.

Residual efficacy of selected larvicides against Culex pipiens pipiens (Diptera: Culicidae) under laboratory and semi-field conditions - Maria K. Sakka; Charalampos S. Ioannou; Nikos T. Papadopoulos; Christos G. Athanassiou (Environmental Science and Pollution Research, 2023)
Mosquitoes are a threat worldwide since they are vectors of important pathogens and parasites such as malaria, dengue, yellow fever, and West Nile. The residual toxicity of several commercial mosquito larvicides was evaluated for the control of Culex pipiens pipiens under controlled laboratory and semi-field conditions during late spring and summer of 2013. The evaluation included six different active ingredient formulations, i.e., diflubenzuron Du-Dim), Bacillus thuringiensis var. israelensis ( Bti ) (Vectobac), spinosad (Mozkill), S-methoprene (Biopren), temephos (Abate), and polydimethylsiloxane (PDMS) (Aquatain), that are currently registered of and had been registered in the past for mosquito control. Under controlled laboratory conditions, the residual activity ranged from 1 week (S-methoprene) up to 2 months (spinosad, PDMS). Exposure of larvicides under semi-field conditions resulted in noticeable differences regarding their efficacy as compared to the laboratory bioassays. Exposure of S-methoprene, Bti , and spinosad, for up to 3 days, resulted in similar adult emergence to the controls. On the other hand, the residual efficacy of diflubenzuron, temephos, and PDMS ranged from 14 to 28 days, depending on the season of exposure. Longevity and fecundity of adults that had emerged from surviving larvae, in most of the cases tested, did not differ significantly from that of the controls. The results of the present study demonstrate the necessity of both field and laboratory studies to draw safe conclusions regarding the efficacy of larvicides against mosquitoes and the selection of the proper formulation for each application scenario. In addition, defining the seasonal variation in the residual toxicity of the tested formulations could be useful for improving mosquitos’ management programs.

Simulated encounters with a novel competitor reveal the potential for maladaptive behavioural responses to invasive species - T. Champneys; K. Ferry; S. Tomkinson; M. J. Genner; C. C. Ioannou (Biological Invasions, 2022)
During the early stage of biological invasions, interactions occur between native and non-native species that do not share an evolutionary history. This can result in ecological naïveté, causing native species to exhibit maladaptive behavioural responses to novel enemies, leading to negative consequences for individual fitness and ecosystem function. The behavioural response of native to non-native species during novel encounters can determine the impact of non-native species, and restrict or facilitate their establishment. In this study we simulated novel encounters between a widespread invasive fish species, the Nile tilapia ( Oreochromis niloticus ), and a threatened native Manyara tilapia ( Oreochromis amphimelas ). In the first experiment single adult O. niloticus were presented with a stimulus chamber (a transparent plastic cylinder) which was empty during control trials and contained a pair of juvenile O. amphimelas in stimulus trials. In the second experiment, the reciprocal set up was used, with pairs of juvenile O. amphimelas as the focal species and adult O. niloticus as the stimulus. Both species approached the stimulus chamber more readily during stimulus trials, a behavioural response which would increase the prevalence of interspecific interactions in situ. This included physical aggression, observed from the competitively dominant O. niloticus towards O. amphimelas . Despite an initial lack of fear shown by O. amphimelas , close inspection of the stimulus chamber often resulted in an energetically costly dart response. Under field conditions we predict that naïve native individuals may readily approach O. niloticus , increasing the likelihood of interactions and exacerbating widely reported negative outcomes.

Valorization of Marine Waste: Use of Industrial By-Products and Beach Wrack Towards the Production of High Added-Value Products - Vita Rudovica; Ana Rotter; Susana P. Gaudêncio; Lucie Novoveská; Füsun Akgül; Linn Kristin Akslen-Hoel; Diogo A. M. Alexandrino; Olga Anne; Lauris Arbidans; Miroslava Atanassova; Magdalena Bełdowska; Jacek Bełdowski; et al. (Frontiers in Marine Science, 2021)
Biomass is defined as organic matter from living organisms represented in all kingdoms. It is recognized to be an excellent source of proteins, polysaccharides and lipids and, as such, embodies a tailored feedstock for new products and processes to apply in green industries. The industrial processes focused on the valorization of terrestrial biomass are well established, but marine sources still represent an untapped resource. Oceans and seas occupy over 70% of the Earth’s surface and are used intensively in worldwide economies through the fishery industry, as logistical routes, for mining ores and exploitation of fossil fuels, among others. All these activities produce waste. The other source of unused biomass derives from the beach wrack or washed-ashore organic material, especially in highly eutrophicated marine ecosystems. The development of high-added-value products from these side streams has been given priority in recent years due to the detection of a broad range of biopolymers, multiple nutrients and functional compounds that could find applications for human consumption or use in livestock/pet food, pharmaceutical and other industries. This review comprises a broad thematic approach in marine waste valorization, addressing the main achievements in marine biotechnology for advancing the circular economy, ranging from bioremediation applications for pollution treatment to energy and valorization for biomedical applications. It also includes a broad overview of the valorization of side streams in three selected case study areas: Norway, Scotland, and the Baltic Sea.

Efficacy of polydimethylsiloxane against Culex pipiens (Diptera: Culicidae) - Anastasia J. Nikolaidou; Charalampos S. Ioannou; Nikos T. Papadopoulos; Christos G. Athanassiou (Environmental Science and Pollution Research, 2021)

The impact of turbidity on foraging and risk taking in the invasive Nile tilapia (Oreochromis niloticus) and a threatened native cichlid (Oreochromis amphimelas) - Jonathan D. B. Wing; Toby S. Champneys; Christos C. Ioannou (Behavioral Ecology and Sociobiology, 2021)
Anthropogenic activity can increase water turbidity, changing fish behaviour by reducing visibility. The spread of invasive species is also facilitated by human activity, further increasing the pressure on native species. In two experiments, we measured the foraging efficiency, risk perception and inter-individual consistency of risk-taking (personality variation in boldness) of an invasive species, the Nile tilapia ( Oreochromis niloticus ), and a threatened tilapia, the Manyara tilapia ( Oreochromis amphimelas ), in clear and turbid water. In experiment one, O . niloticus was faster to initiate feeding, encountered more food items and consumed more than O . amphimelas. The latency to start foraging by O . niloticus decreased in turbid water. Turbidity did not affect the latency to start foraging in O . amphimelas but the number of food items they encountered was highest at the intermediate turbidity. There was however no significant effect of turbidity in either species on the total food consumed. In contrast to this foraging context, in experiment two with a refuge and no food available, risk taking behaviour was similar in both species and they both responded with similarly reduced risk taking in turbid water. Evidence of personality variation was weak, being observed only in O. amphimelas when first leaving the shelter in turbid water. Overall, species differences were greater in the foraging context but turbidity was more important in the risk-taking context. O. amphimelas is more sensitive to turbidity during foraging, and O . niloticus is likely to have a competitive advantage in foraging situations, especially in degraded turbid habitats . Significance statement Under human-induced environmental change, native species are often exposed to multiple stressors. Here, we tested the responses of two cichlid fish to increasing turbidity, the Nile tilapia ( Oreochromis niloticus ), which is invasive throughout the tropics, and the Manyara tilapia ( Oreochromis amphimelas ), a threatened species, indigenous to Tanzania. We found that turbidity was beneficial to the foraging of O . niloticus , which in both clear and turbid water consumed and encountered more food than O. amphimelas . In contrast, without food present, both species displayed similar responses of increased risk perception in turbid water with little evidence of personality variation between individuals in either species. Our results suggest that invasive species tolerant of degraded habitats may outcompete less well-adapted native species for food.

Current Insights into Fatty Acid Transport in the Brain - Maria S. Ioannou (The Journal of Membrane Biology, 2020)

Removal of Chromium from Soils Cultivated with Maize (Zea Mays) After the Addition of Natural Minerals as Soil Amendments - A. Μolla; Z. Ioannou; S. Mollas; E. Skoufogianni; A. Dimirkou (Bulletin of Environmental Contamination and Toxicology, 2017)

Polygyny in the olive fly—effects on male and female fitness - C. D. Gerofotis; B. Yuval; C. S. Ioannou; C. T. Nakas; N. T. Papadopoulos (Behavioral Ecology and Sociobiology, 2015)

‘No thanks’—reasons why pregnant women declined an offer of cystic fibrosis carrier screening - L. Ioannou; J. Massie; S. Lewis; B. McClaren; V. Collins; M. B. Delatycki (Journal of Community Genetics, 2014)

Zooplankton diversity and distribution in a deep and anoxic Mediterranean coastal lake - G. KEHAYIAS; A. RAMFOS; S. IOANNOU; P. BISOUKI; E. KYRTZOGLOU; A. GIANNI; I. ZACHARIAS (Mediterranean Marine Science, 2013)
The variation of the smaller size fraction of zooplankton was investigated during a two-year period in a brackish deep and anoxic coastal lake of western Greece (Aitoliko), along with the specific environmental characteristics of this ecosystem. The zooplanktonic community comprised a relatively small number of taxa and it was dominated by brackish-water calanoid copepods (Paracartia latisetosa, Calanipeda aquaedulcis) and in certain periods by rotifers and tintinnids. The zooplankton abundance showed an increase in the warmer period starting from late spring and reached maximum values in July. In the well oxygenated surface layer, temperature was the most important parameter influencing the seasonal cycles of all groups. In contrast, the oxygen depletion a few meters under the surface affected the vertical distribution of most of the zooplankton groups, which were found restricted in the surface layer especially from spring until autumn. Only the meroplanktonic larvae of polychaetes presented increased proportions in the deeper layers. Salinity has not significantly influenced the zooplanktonic assemblages. The results point out the degraded status of the Aitoliko basin where the hypoxic/anoxic layers resulted to a high portion of dead organic material identified as copepod carcasses, and underlines the necessity of monitoring of this ecosystem.

Zooplankton diversity and distribution in a deep and anoxic Mediterranean coastal lake - G. KEHAYIAS; A. RAMFOS; S. IOANNOU; P. BISOUKI; E. KYRTZOGLOU; A. GIANNI; I. ZACHARIAS (Mediterranean Marine Science, 2013)

Mycotoxin contamination of cereal grain commodities in relation to climate in North West Europe - H.J. Van Der Fels-Klerx; S. Klemsdal; V. Hietaniemi; M. Lindblad; E. Ioannou-Kakouri; E.D. Van Asselt (Food Additives & Contaminants: Part A, 2012)

Hierarchical radial and polar organisation of chromosomes in human sperm - N. M. Millan; P. Lau; M. Hann; D. Ioannou; D. Hoffman; M. Barrionuevo; W. Maxson; S. Ory; H. G. Tempest (Chromosome Research, 2012)

Inventory of alien marine species of Cyprus (2009) - S. KATSANEVAKIS; K. TSIAMIS; G. IOANNOU; N. MICHAILIDIS; A. ZENETOS (Mediterranean Marine Science, 2009)
An updated inventory of alien marine species from coastal and offshore waters of Cyprus is presented. Records were compiled based on the existing scientific and grey literature, including HCMR database of Mediterranean alien species, technical reports, scientific congresses, academic dissertations, and websites, as well as on unpublished/personal observations. The listed species were classified in one of five categories: established, invasive, casual, cryptogenic, and questionable. The mode of introduction and the year of first sighting were also reported for each species. Eight new records based on personal observations of the authors were reported (Chondria coerulescens, Neosiphonia sphaerocarpa, Enchelycore anatina, Lagocephalus spadiceus, Lagocephalus suezensis, Scomberomorus commerson, Sillago sihama, and Sphoeroides pachygaster). Nine species, previously reported as aliens in Cypriot waters, were excluded from the inventory for various reasons. Ten established species were characterized as invasive (Caulerpa racemosa var. cylindracea, Cerithium scabridum, Strombus persicus, Trochus erythraeus, Brachidontes pharaonis, Pinctada radiata, Fistularia commersonii, Lagocephalus sceleratus, Siganus luridus, and Siganus rivulatus) as they have a substantial impact on biodiversity and/or local economy. The impact of alien marine species in Cyprus is expected to grow in the close future, and further effort directed towards recording alien invasions and their impact will be needed.

HPLC Determination of Mepiquat Chloride in Commercial Pesticide Formulations - H. Karasali; S. Ioannou (Bulletin of Environmental Contamination and Toxicology, 2009)

A 191-kb genomic fragment containing the human α-globin locus can rescue α-thalassemic mice - Keith Al-Hasani; Jim Vadolas; Anja S. Knaupp; Hady Wardan; Lucille Voullaire; Robert Williamson; Panayiotis A. Ioannou (Mammalian Genome, 2005)

Multicenter randomized trial of fluconazole versus amphotericin B for treatment of candidemia in non-neutropenic patients - P. Phillips; S. Shafran; G. Garber; C. Rotstein; F. Smaill; I. Fong; I. Salit; M. Miller; K. Williams; J. M. Conly; J. Singer; S. Ioannou (European Journal of Clinical Microbiology & Infectious Diseases, 1997)